Interlanguage Pragmatics Failure among Javanese Learners of Japanese - Rina Supriatnaningsih; Tatang Hariri; Djodjok Soepardjo; Lisda Nurjaleka; Silvia Nurhayati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
In the Japanese language, Keigo refers to the politeness in language that one must adhere to during interactions with native speakers. Japanese language students are obliged to pay attention to this principle and behave politely in spoken communication. In the Javanese language, the manner in which speech is delivered, undha usuk, comprises a variety of registers applied to different social contexts, such as krama (High or formal Javanese) and ngoko (Low or vernacular Javanese). Still, other politeness principles are to be taken into account. This study, driven by such a concern, was devoted to examining politeness violations in communications between 108 university students, most of whom were native Javanese speakers. The politeness principle was employed to unravel the issue. Data were collected by recording conversations between participants and native Japanese speakers. A follow-up interview with each subject was also conducted. The results revealed that most students failed to build intercultural communication in Japanese conversation, due to their lack of socio-pragmatic knowledge. Based on the interview results, in daily communication, the students rarely used the Javanese speech act level of krama, instead using basa ngoko or Indonesian. These findings emphasize the socio-pragmatic concept, and more precisely the politeness principles other than the Keigo style, to students. This should minimize the violation of politeness maxims in the Japanese language.